2020
DOI: 10.1242/dev.193029
|View full text |Cite
|
Sign up to set email alerts
|

Tek/Tie2 is not required for cardiovascular development in zebrafish

Abstract: Angiopoietin/TIE signalling plays a major role in blood and lymphatic vessel development. In mouse, Tek/Tie2 mutants die prenatally due to a severely underdeveloped cardiovascular system. In contrast, in zebrafish, previous studies have reported that while embryos injected with tek morpholinos (MOs) exhibit severe vascular defects, tek mutants display no obvious vascular malformations. To further investigate the function of zebrafish Tek, we generated a panel of loss-of-function tek mutants, including RNA-less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 94 publications
3
23
0
1
Order By: Relevance
“…Our present data show for the first-time in vivo evidence that angpt1 and itgb1b play not only essential roles in developing cerebrovascular formation but exert also own neurogenic effects on the development of different neural cell populations, including dopaminergic, histaminergic, and GABAergic systems, and the patterning of hindbrain reticulospinal neurons in the CNS. Our novel findings also provide evidence that the role of tek is dispensable in embryonic neurogenesis in zebrafish, similar to the published results in angiogenesis (Gjini et al, 2011; Jiang et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our present data show for the first-time in vivo evidence that angpt1 and itgb1b play not only essential roles in developing cerebrovascular formation but exert also own neurogenic effects on the development of different neural cell populations, including dopaminergic, histaminergic, and GABAergic systems, and the patterning of hindbrain reticulospinal neurons in the CNS. Our novel findings also provide evidence that the role of tek is dispensable in embryonic neurogenesis in zebrafish, similar to the published results in angiogenesis (Gjini et al, 2011; Jiang et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the gross cardiovascular phenotype appearing in the angpt1 sa14264 mutant and reported itgb1b mi371 mutant (Iida et al, 2018), the tek hu1667 mutant fish grow naturally without overt cardiovascular defects (Gjini et al, 2011; Jiang et al, 2020). It has been reported that besides Tek, Angpt1 can bind to integrins and activate similar pathways as the angpt1-tek does (Chen et al, 2009a), which renders it possible that the angpt1-itgb1b signaling pathway may play a more vital role than the recognized angpt1-tek pathway in the regulation of embryogenesis.…”
Section: Resultsmentioning
confidence: 93%
“…RBF orthologs were identified with the targeted ortholog search tool fDog ( Jiang et al, 2020 ) 2 using the following parameter settings: –checkCoorthologsRef, −-countercheck, −-minDist=family, and −-maxDist=kingdom. Protein domain architectures were compared pair-wise between each seed protein and its orthologs, and an architecture similarity score was computed with FAS 3 implemented into fDOG.…”
Section: Methodsmentioning
confidence: 99%
“…The latter problem can be ameliorated by scoring the similarity of protein domain architectures ( Koestler et al, 2010 ), which comprise features, such as Pfam ( El-Gebali et al, 2019 ) or Smart ( Letunic et al, 2009 ) domains, transmembrane regions, signal peptides, or regions of biased amino acid composition. Differences in domain architectures can then indicate alterations in the respective functional spectra of the compared proteins ( Jiang et al, 2020 ). In contrast to the ample means to cope with the spurious inference of archaeal RBF candidates based on homologous proteins, false negatives, i.e., proteins overlooked in the homolog searches because their sequences have diverged to an extent that they are no more similar than it is expected by chance, have received very little attention.…”
Section: Introductionmentioning
confidence: 99%
“…This caused a significant shift in how morpholinos are used in the laboratory [ 15 ] and promoted the adoption of CRISPR/Cas9 and similar gene editing techniques to create mutant allele-harbouring zebrafish lines. Their study also prompted a more nuanced understanding of what underlying biological mechanisms can cause this discrepancy, ranging from within-pathway compensation to cellular stress response and evolutionary divergence of protein function [ 16 , 17 , 18 , 19 ].…”
Section: The Endothelium In Heart Developmentmentioning
confidence: 99%